Jump Diffusion Modelling for the Brazilian Short-Term Interest Rate - José Carlos Nogueira Cavalcante Filho; Edson Daniel Lopes Gonçalves (BBR: Brazilian Business Review)
In order to capture the informational effect of the Brazilian short-term interest rate (SELIC rate) by Poisson jumps, we build on the tests condu cted by Das (2002) and Johannes (2004), which show the significance of such structures for U.S. Federal Open Market Committee (FOMC) announcements. As in the above researches, w e have found evidence that a relevant amount of the short-term volatility in the fixed in come market is captured by introducing jumps on the stochastic process of the short-term r ate. This structure also allows the verification of the information content of specific events, such as Brazilian monetary policy authority (COPOM) meetings and public bond auctions.